The relationship between condictio and version in REM in modern law - Stefanović Aleksandra (Glasnik Advokatske komore Vojvodine, 2023)
In this paper, the author analyses a lawsuit for unjust enrichment through the prism of two institutes: condictio and actio de in rem verso. The origin of these two notions is linked to Roman law, although their essence has been drastically changed in modern law. It is necessary to determine them in relation to other lawsuits in order to further clarify the boundaries of these institutes through negative definitions as a preliminary step in this presentation. It is necessary to determine their mutual similarities and differences, as well as different understandings of the institutes, depending on the point of view of the legal system in terms of regulating the lawsuit for unjust enrichment, in order to adequately compare them. Comparative law and dogmatic methods were used in the paper.